2021
DOI: 10.1155/2021/5671998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Specific Acupuncture Therapy Combined with Rehabilitation Training on Incomplete Spinal Cord Injury: A Randomized Clinical Trial

Abstract: Acupuncture therapies were used to treat spinal cord injury (SCI) and its complications. To assess the effect of a specific acupuncture therapy combined with rehabilitation training for inpatients with incomplete SCI, we conducted an assessor-blinded, randomized controlled clinical trial in the Department of Rehabilitation Medicine Center in West China Hospital, Sichuan University. Seventy-two participants diagnosed with incomplete SCI were randomly assigned into 3 groups of 24 patients each, with data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our findings suggest that inpatient rehabilitation may be associated with neurological recovery. Xiong et al [ 27 ] also reported that specific acupuncture therapy combined with rehabilitation training could promote neurological recovery in patients with incomplete SCI. Therefore, for patients with TSCI, especially for motor complete injury, rehabilitation therapy plays an irreplaceable role in the recovery of neurological function.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that inpatient rehabilitation may be associated with neurological recovery. Xiong et al [ 27 ] also reported that specific acupuncture therapy combined with rehabilitation training could promote neurological recovery in patients with incomplete SCI. Therefore, for patients with TSCI, especially for motor complete injury, rehabilitation therapy plays an irreplaceable role in the recovery of neurological function.…”
Section: Discussionmentioning
confidence: 99%